2021
DOI: 10.1128/jvi.00912-21
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of TAX1BP1 Amplifies Innate Immune Responses during Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the main cause of acute respiratory infections in young children, and also has a major impact on the elderly and immunocompromised people. In the absence of a vaccine or efficient treatment, a better understanding of RSV interactions with the host antiviral response during infection is needed. Previous studies revealed that cytoplasmic inclusion bodies (IBs) where viral replication and transcription occur could play a major role in the control of innate immunity during infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Based on this clarified mechanism of the A20 protein complex [111] and the recent findings that RSV N interacts with TAX1BP1 [106], we could hypothesize that RSV N facilitates the assembly of this multiprotein complex (Figure 5). In this way, RSV N would be able to restrain the innate immune response during infection.…”
Section: Rsv N Might Downregulate Nf-κb and Irf3/7 Signalingmentioning
confidence: 67%
See 2 more Smart Citations
“…Based on this clarified mechanism of the A20 protein complex [111] and the recent findings that RSV N interacts with TAX1BP1 [106], we could hypothesize that RSV N facilitates the assembly of this multiprotein complex (Figure 5). In this way, RSV N would be able to restrain the innate immune response during infection.…”
Section: Rsv N Might Downregulate Nf-κb and Irf3/7 Signalingmentioning
confidence: 67%
“…In parallel, higher levels of IFN-α and TNF-α were detected in the lungs of TAX1BP1 knockout mice compared to wildtype mice. Infection of alveolar macrophages isolated from TAX1BP1 knockout mice resulted in enhanced secretion of antiviral and inflammatory cytokines compared to RSVinfected macrophages isolated from wild-type mice [106]. These findings suggest a proviral role of TAX1BP1 during RSV replication by participating in the attenuation of the host antiviral and inflammatory response.…”
Section: Rsv N Might Downregulate Nf-κb and Irf3/7 Signalingmentioning
confidence: 77%
See 1 more Smart Citation
“…Depletion of WDR5 has been shown to enhance the induction of IFN-β during MeV infection ( 67 ). Additionally, the Tax1-binding protein 1 (TAX1BP1), which is directly involved in the negative regulation of NF-κB and IRF3 signaling pathways, has been identified as a cellular partner of RSV N protein ( 174 ). The depletion of TAX1BP1 resulted in enhanced antiviral and inflammatory responses and restricted RSV replication.…”
Section: Viruses Employ Diverse Strategies For Immune Evasion ...mentioning
confidence: 99%
“…In line with this, our group found that downregulation of A20, TAX1BP1, or ABIN1 in HRSV infection increased the early innate immune response and reduced virus production in epithelial cells [ 108 ]. Accordingly, enhanced expression of inflammatory and anti-viral cytokines has been observed in TAX1BP1 knockout mice infected with HRSV [ 32 ].…”
Section: Introductionmentioning
confidence: 99%